CLT (Cross Laminated Timber): Produksi, Karakteristik dan Perkembangannya (CLT (Cross Laminated Timber): Production, Characteristics and Development) - Lestari, Ratri Yuli (Kementerian Perindustrian, 2017)
Cross laminated timber (CLT) is an engineered wood product as a laminated board that was arranged in cross order and applied as floor, roof, and wall. This product is an innovation in overcoming the scarce of wood material especially in large diameter and high quality as a building material. The review discusses the history of CLT, the characteristics, and its developments. CLT was first developed in Europe especially in Austria and Germany and then spread around the world. CLT has superiority in term of characteristics such as renewable, recyclable, easy to design and form, good insulation, energy efficient, fire resistance, good seismic characteristics, and also acts as a carbon sink that relieves the stress of global greenhouse gasses effect. CLT also has the strength that comparable to concrete and steel, and suitable for high rise building structure purposes. CLT is a prefabricated product and has advantages such as time saving, labor efficient, minimal post construction waste, and less disturbance to the environment during construction. CLT was developed outside Europe and reached North America, New Zealand and Indonesia. The barrier in adopting CLT are the lack of information of the products. One of the solution is to increase the awareness and the product knowledge.Keywords : architecture, building constructions, cross laminated timber, engineered wood